A construção do texto: do oral ao escrito a retextualização - Silva, Edson Santana da (2016)
The aim of this dissertation, held at the Postgraduate Studies Programme in Portuguese at Pontifícia Universidade Católica de São Paulo, is to study the construction and textual organization from the perspective of retextualization activity, taking the oral form of the language as the basis to obtain satisfactory results in the written text. At school, writing is usually taken as an object of study at the expense of orality. However, in the last decades, in Brazil, the development of linguistic research lines that put the two modes of language - oral and written - at the same level has allowed greater recognition of orality and hence greater concern and further studies on the strategies carried out in the passage of the spoken text to written text. Our main objective is discuss some pedagogical approaches to work with text construction, through retextualization. The specific objectives are: 1. Identify the structure and functional characteristics of the oral form. 2. Identify the structure and characteristics of the written form. 3. Show similarities and differences between the oral and written forms. 4. Introduce a proposal to teach the textual production through the retextualization process aiming at the communicative competence of the student. The theories that support this research is the analysis of conversation, interactional sociolinguistics and textual linguistics. The first and second theories deal with the study of the organization, construction and the main aspects of the oral discourse, especially as a contextualized practice. The third one has provided information for the understanding and teaching of text production